A High‐Performances Flexible Temperature Sensor Composed of Polyethyleneimine/Reduced Graphene Oxide Bilayer for Real‐Time Monitoring. Issue 3 (15th January 2019) - Liu, Qingxia; Tai, Huiling; Yuan, Zhen; Zhou, Yujiu; Su, Yuanjie; Jiang, Yadong
Abstract: The temperature sensors are urgently required for real‐time temperature monitoring in healthcare, disease diagnosis, and other areas. In this work, a skin‐attachable flexible temperature sensor composed of polyethyleneimine/reduced graphene oxide bilayer is developed on polyimide substrate by a facile spray‐dipping process. The spectroscopy properties of sensing films are examined and analyzed in details and demonstrated the partial reduction of graphene oxide film. The prepared sensor exhibits high sensitivity (1.30% °C −1 ), linearity ( R 2 = 0.999), accuracy (0.1 °C), and durability (60 d) for temperature sensing between 25 and 45 °C, which can fully satisfy the requirements of real‐time and long‐term skin temperature monitoring. Additionally, the practical applications in monitoring human skin temperature, breathing rate, finer touch, blow, and water droplet are performed, revealing its great potential in e‐skin, disease diagnosis, healthcare, and other fields. Abstract : The real‐time temperature sensors are urgently required in lots of fields. A skin‐attachable polyethyleneimine/reduced graphene oxide bilayer temperature sensor fabricated through a facile spray‐dipping method exhibits excellent performances in real‐time and long‐term temperature monitoring. The notable sensitivity, resolution, stability, and durability are essential to the temperature monitoring and open up a new window for broad applications in other scenarios.